Resistindo às pressões dos conservadorismos, apesar de tudo - Minella, Luzinete Simões; Ramos, Tânia Regina de Oliveira; Lago, Mara Coelho de Souza; Wolff, Cristina Scheibe (Revista Estudos Feministas, 2020)
.